The Palace of Illusions – A Feministic Purview - Jerome, J. Charly; Geetha, P.; Vijayalakshmi, R. (International Journal of Psychosocial Rehabilitation, 2020)
An eccentric abolishing of cultural and psychological repressions on women with unconscious potentiality to close the phallocentric language is ecriture feminine. Production of literary genre by a woman writer explores the diversity with fluidity and rationality. Recreation of epics in the hands of Women writers incarnate the story from women‟s perspective and recreates the women characters to attain female consciousness in the patriarchal society. The Palace of illusions humanizes the character of Draupadi rather than feminizing and attributing feminine qualities. Draupadi‟s inner voice and secret desires reveal the liberal human and her spirit to be liberated for the cause. Even though there had been social injustice caused to Draupadi in Mahabharatha, the very effect of the affront reveals the determination of one-woman character among the five irresolute men. The story truly revolves around how Draupadi rises above the destiny designed for her and liberates her soul with an overwhelming rendering of support to the women community. Purpose of life relies highly on the existence of humanism amidst the existing difference in the name of caste, colour, class, creed and most significantly gender. The paper aims to discuss the psyche of Draupadi that transforms, liberates and survives as Paanchali and gives voice to the desired change of humanistic attitude to maximize the well-being of women.